Effects of CYP46A1 Inhibition on Long-Term-Depression in Hippocampal Slices ex vivo and 24S-Hydroxycholesterol Levels in Mice in vivo - Popiolek, Michael; Izumi, Yukitoshi; Hopper, Allen T.; Dai, Jing; Miller, Silke; Shu, Hong-Jin; Zorumski, Charles F.; Mennerick, Steven (Frontiers in Molecular Neuroscience, 2020)
The manipulation of cholesterol and its metabolites has been hypothesized to be therapeutically beneficial for mood disorders, neurodegenerative disorders, and epilepsies. A major regulator of cholesterol clearance and turnover in the central nervous system is CYP46A1, a brain enriched enzyme responsible for metabolism of cholesterol into 24S-hydroxycholesterol. Inhibition of this enzyme may negatively modulate NMDARs as 24S-hydroxycholesterol was shown to enhance NMDAR function. In addition, alterations of local cholesterol or other changes mediated by CYP46A1 activity could have important influences on central nervous system function. Here we demonstrate that humans and mice display brain region specific and similar CYP46A1 and 24S-hydroxycholesterol distribution. Treatment with distinct classes of CYP46A1 inhibitors led to central 24S-hydroxycholesterol reduction in vivo and an ablation of long term depression in hippocampal slices. Our results suggest that rodents show similarity to humans for studying the impact of CYP46A1 inhibitors and that rapid, local modulation of oxysterols can be achieved through CYP46A1 inhibition.